Analisis Faktor dan Dampak yang Mempengaruhi Hengkangnya Penanaman Modal di kota Batam - Lu Sudirman; Indah Novita (Fakultas Hukum, Universitas Internasional Batam, 2018)
Investment is any form of investment activities either by domestic investment or foreign investor to do business in the territory of the Republic of Indonesia, which aims to increase national economic growth, create employment, promote sustainable economic development, improve business competitiveness national, enhancing the capacity and capability technology, cultivating the potential economy into real economic power by using the funds originating, improving the welfare of the community. Investment is essentially the first step in economic development activities. However, the fact that is happening in the field today is the number of companies that closed the city batam increasing from 2014 to 2017 in the city of Batam. This causes the number of unemployed to increase. The research method used in this research is the method of legal juridical empirical research with qualitative approach that analyzes the synchronization of regulations that apply to the facts that occur in the field. Investment in Indonesia is regulated in Law Number 25 Year 2007 regarding Capital Investment. Investors consider that the Government through the Act as the main legal umbrella in the field of investment that regulates the policies on investment. It is seen that the government's policies do not work with as regulated in the Investment Law. This Government should play an important role in overcoming the emergence of factors that cause the impact of economic growth on the departure of investment in Batam city. If the government's follow-up is consistent and committed.